1971
DOI: 10.1111/eci.1971.1.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic and Portal Venous Transport of α‐Tocopherol and Cholesterol

Abstract: The absorption of 3H‐α‐tocopherol was studied in rats after intraduodenal administration in micellar solutions. Net absorption from mixed micelles in lymph fistula rats was 66%, but only 42% appeared in lymph and 3% was excreted in urine. Administration of 3H‐α‐tocopherol in taurocholate micelles reduced both the rate of absorption into lymph and the proportion carried in chylomicrons. In studies with lymph and bile duct cannulated rats, up to 8% of the radioactivity was excreted in bile, irrespective of wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Depending on the form and formulation tested, the extent of absorption varied between 10 and 65%, probably reflecting differences during the intraluminal phase of absorption. Although there is evidence that some of the a-tocopherol may be taken up by the portal system (MacMahon et al 1971;Hollander & Dadufalza, 1989), at least the majority of the absorbed tocopherol is carried via the lymphatics to the bloodstream. …”
Section: Symposium On 'Micronutrient Transport Processes' Tocopherol mentioning
confidence: 99%
“…Depending on the form and formulation tested, the extent of absorption varied between 10 and 65%, probably reflecting differences during the intraluminal phase of absorption. Although there is evidence that some of the a-tocopherol may be taken up by the portal system (MacMahon et al 1971;Hollander & Dadufalza, 1989), at least the majority of the absorbed tocopherol is carried via the lymphatics to the bloodstream. …”
Section: Symposium On 'Micronutrient Transport Processes' Tocopherol mentioning
confidence: 99%
“…On the other hand, studies by Kelleher et al (11) and Brink et al (12) using fecal excretion as a measure of unabsorbed tocopherol amounts showed decreased absorption at high dose levels compared to lower dose levels. The absorbed tocopherols are secreted into the lymphatics associated with chylomicrons (13,14), although small amounts can be transported from the intestine via the portal vein, but this is only a minor pathway under normal circumstances (15). From the lymphatics chylomicrons enter the circulation where they are catabolized.…”
mentioning
confidence: 99%
“…Infusion of radiolabeled tocopherols or large amounts of unlabeled standards followed by estimation of the amount transported in lymph is widely used to measure absorbed amounts (13,15,19,20). Vegetable oils are among the richest sources of vitamin E in the diet (21,22).…”
mentioning
confidence: 99%
“…The major increase in liver level reported by Kelleher et al (13), when tracer doses of oral tocopherol were dissolved in Tween 80, presumably reflects the same mechanism and might suggest that detergents favoured increased absorption by the portal route (15).…”
Section: Discussionmentioning
confidence: 91%
“…The faecal excretion of radioactivity represents tocopherol which is not absorbed plus that which is secreted in the bile and not re-absorbed, but this latter is only a minor proportion of the faecal output (15,17). Absorption of a-tocoph erol and the effect of cholestyramine were similar to the values reported by Davies et al (7).…”
Section: Discussionmentioning
confidence: 99%